The Education of Things in Italy. Programs, Books, and Authors.: - Bianchini, Paolo; Pongiluppi, Francesco; Serrao, Paula Alejandra (Historia y Memoria de la Educación, 2024)
This article analyzes the diffusion, transformations, appropriation, and Italian translation of the "object lessons" between the late 19th and early 20th centuries. Beginning with an analysis of the pedagogical and philosophical roots of the “object lessons," the paper traces their introduction to the Peninsula through the study of Italian educational reforms and programs of the period. In addition, it examines a series of authors and schoolbooks of “object lessons," considered fundamental for understanding the Italian case. Finally, it indicates some lines of research to further deepen the argument, which still has few studies.